Transforming Photocatalytic g‐C3N4/MoSe2 into a Direct Z‐Scheme System via Boron‐Doping: A Hybrid DFT Study - Ai, Changzhi; Li, Jin; Yang, Liang; Wang, Zhipeng; Wang, Zhao; Zeng, Yamei; Deng, Rong; Lin, Shiwei; Wang, Cai‐Zhuang (ChemSusChem, 2020)
Z‐scheme photocatalytic systems are an ideal band alignment structure for photocatalysis because of the high separation efficiency of photo‐induced carriers while simultaneously preserving the strong reduction activity of electrons and oxidation activity of holes. However, the design and construction of Z‐scheme photocatalysts is challenging because of the need for appropriate energy band alignment and built‐in electric field. Here, we propose a novel approach to a Z‐scheme photocatalytic system using density functional theory calculations with the HSE06 hybrid functional. The undesirable type‐I g‐C3N4/MoSe2 heterojunction is transformed into a direct Z‐scheme system through boron doping of g‐C3N4 (B‐doped C3N4/MoSe2). Detailed analysis of the total and partial density of states, work functions and differential charge density distribution of the B‐doped C3N4/MoSe2 heterojunction shows the proper band alignment and existence of a built‐in electric field at the interface, with the direction from g‐C3N4 to MoSe2, demonstrating a direct Z‐scheme heterojunction. Further investigation on the absorption spectra reveals a large enhancement of the light absorption efficiency after boron doping. The results consistently confirm that electronic structures and photocatalytic performance can be effectively manipulated by a facile boron doping. Modulating the band alignment of heterojunctions in this way provides valuable insights for the rational design of highly efficient heterojunction‐based photocatalytic systems. Boron‐induced transformation: Boron doping into g‐C3N4 significantly transforms the g‐C3N4/MoSe2 heterojunction from type‐I into a direct Z‐scheme system by rationally modulating the band alignment of the two photocatalysts. Electron–hole pairs are effectively separated, preserving the strong reduction ability of the electrons and oxidation ability of the holes. Light absorption of the B‐doped g‐C3N4/MoSe2 heterojunction is also enhanced after boron doping and the photocatalytic performance is increased.